Application of Automatic Queuing Models for Visiting Pilgrimage - Purohit, Jagdish C.; Belwal, O.K. (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2015)
Pilgrimage in the Indian is growing consistently and is an important attraction and destination for both foreign and domestic. Queuing for an explicit service according to the needs of venerator in the process of moving to a specific sequence .This can be done by a queue-based scheduler. This paper focuses on a system revered place and the average waiting time of venerator service is the revered place that different queuing algorithms. The purpose of this paper is to develop queuing system for organizing sacred place to build automated queue status analyzes and to service the venerator. New queuing design model test results and the average waiting time varies according to factors that can switch between scheduling algorithms. The main novelty of this work is the average waiting time modeling that gives the best average waiting time scheduling algorithm with the process of switching in addition, concerns have taken in processing.